2016
DOI: 10.1128/jcm.00529-16
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Xpert HPV Point-of-Care Test for Detection of Human Papillomavirus Infection by Use of Self-Collected Vaginal and Clinician-Collected Cervical Specimens

Abstract: iThe World Health Organization has recommended that testing for high-risk human papillomavirus (HPV) (hrHPV) infection be incorporated into cervical screening programs in all settings worldwide. In many high-burden, low-income countries, it will not be feasible to achieve high cervical screening coverage using hrHPV assays that require clinician-collected samples. We conducted the first evaluation of self-collected vaginal specimens compared with clinician-collected cervical specimens for the detection of hrHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 10 publications
3
74
1
Order By: Relevance
“…Other more feasible methods include HPV DNA testing and visual inspection with acetic acid (VIA). HPV DNA testing has been shown to be an effective test for primary cervical screening (61), and a few studies have even shown promising results from using self-collection methods in LMICs (62)(63)(64). VIA can be successfully performed by trained mid-level providers (65).…”
Section: Cervical Cancermentioning
confidence: 99%
“…Other more feasible methods include HPV DNA testing and visual inspection with acetic acid (VIA). HPV DNA testing has been shown to be an effective test for primary cervical screening (61), and a few studies have even shown promising results from using self-collection methods in LMICs (62)(63)(64). VIA can be successfully performed by trained mid-level providers (65).…”
Section: Cervical Cancermentioning
confidence: 99%
“…Given that one of the fundamental advantages of HPV testing is that it can be done with self-collected vaginal specimens, two central questions of HPV self-sampling relate to its diagnostic accuracy and the performance and acceptability of the sampling device. Several studies that compared vaginal self-sampling with cervical physician-sampling found high concordance for HPV detection (1,(11)(12)(13)(14)(15)(16)(17)(18) and comparable clinical accuracy to detect high-grade cervical intraepithelial neoplasia (CIN) and cancers, provided that validated assays are used (17,(19)(20)(21)(22). In a recent meta-analysis of 56 accuracy studies, the pooled relative sensitivity of high-risk HPV (hrHPV) assays (based on PCR) on self-collected versus physician-collected samples was 99% for CIN2 þ or CIN3 þ , and the positive predictive values (PPV) for either histologic endpoint were not significantly lower for self-collected samples (22).…”
Section: Introductionmentioning
confidence: 99%
“…A CHW goes door-todoor asking women to participate in a baseline survey, offers participants sexually transmitted infection (STI) and cervical cancer health education, and provides them with instructions on how to self-collect for CCS. The specimen is then dropped at a HCII or HCIII by the CHW and transported to a central laboratory at a local health centre for testing using GeneXpert point of care [22]. Samples are not banked and swabs are destroyed after testing.…”
Section: Arm1: Door-to-doormentioning
confidence: 99%